Mixed Marriage Law On Marital Property Due To Divorce - Justicia Firdaus Kurniawan; Dominikus Rato; Moh Ali (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Marriage is a relationship that unites two different individuals, men and women in a bond, namely a legal marriage bond. In Article 1 of Law Number 1 of 1974 concerning Marriage, it is explained that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. In social life, especially in Indonesia, it is possible to have a marriage between an Indonesian citizen and a foreign citizen or commonly called a mixed marriage. In Article 57 of Law Number 1 of 1974 concerning Marriage, it is explained that what is meant by mixed marriage in this Law is a marriage between two people who in Indonesia are subject to different laws, due to differences in citizenship and one of the parties is an Indonesian citizen. During the marriage period there is a joint property, regarding the position in Article 35 paragraph 1 of Law Number 1 of 1974 concerning Marriage, it is explained that assets obtained during marriage become joint assets.